Clinical evolution of cases of cutaneous leishmaniasis in Brazil: A time frame (Research, Society and Development, 2024)
Objective: To analyze the evolution of American Tegumentary Leishmaniasis (ATL) cases in Brazil between 2018 and 2022, highlighting regional differences and the effectiveness of public health interventions. Methodology: Observational epidemiological study using a time series analysis, based on data from the Notifiable Diseases Information System (SINAN). Data collection took place between May and June 2024, and descriptive and comparative statistics were used for analysis. Results and Discussion: A total of 82,204 ATL cases were reported in Brazil during the study period, with the highest incidence in the Northern region. There were significant annual and regional variations, reflecting the complexity of the disease and the need for continuous surveillance. The cure rate was high, but cases of abandonment, transfers, and deaths highlight ongoing challenges in disease control. Conclusion: ATL remains a significant public health issue in Brazil, particularly in the Northern and Northeastern regions. Improvements in diagnostic, treatment, and surveillance strategies are crucial to reducing the morbidity and mortality associated with the disease.